Impact of COVID-19 and Nonpharmaceutical Interventions on Common Respiratory Viruses in Children: A 5-Year Study in Hangzhou, China - Zhou, Jianming; Sun, Yanhong; Shen, Hao; Yang, Liuqiao; Ye, Qing; Zhu, Hongmei; Zhu, Zhiwen (Intervirology, 2025)
Background: Nonpharmaceutical Interventions (NPIs) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) not only curbed the spread of novel coronavirus (COVID-19) but also affected common respiratory viruses infected by children. Methods: Samples of children diagnosed with respiratory tract infection in Children’s Hospital affiliated with Zhejiang University from January 2019 to December 2023 were collected, and ADV, Flu A, Flu B, and RSV were detected. Statistical analysis was carried out with R software. Results: From January 2019 to December 2023, a total of 684,413 samples were tested, including 369,620 males, accounting for 54.01%, and 314,793 females, accounting for 45.99%. Among them, there were 213,443 positive samples (31.19%), of which 40,484 ADV-positive samples (18.97%), 106,423 Flu A-positive samples (49.86%), 32,379 Flu B-positive samples (15.17%), 30,776 RSV-positive samples (14.42%), and 3,381 mixed infection samples (1.58%). Among children of different ages in Hangzhou before, during and after COVID-19, the highest total detection rate of respiratory virus was 4–6 years old (accounting for 36.69%), followed by >7 years old (accounting for 35.10%). The distribution in different seasons shows that the number of children infected with respiratory viruses reaches a peak in winter and spring. Compared with 2019 (33.20%) before the COVID-19 epidemic, the total detection rate of common respiratory viruses in children was lower during the COVID-19 pandemic (24.54% in 2020–2022), and it was increased in 2023 after NPIs were cancelled (accounting for 35.20%). Conclusion: NPI measures can effectively reduce the spread of common respiratory viruses, Lifting of NPIs can lead children to an increase viral infection rate, particularly in Flu A.